2005
DOI: 10.1016/j.cam.2005.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Exponential stability in p-th mean of solutions, and of convergent Euler-type solutions, of stochastic delay differential equations

Abstract: Exponential stability in p-th mean of solutions, and of convergent Euler-type solutions, of stochastic delay differential equations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(101 citation statements)
references
References 15 publications
1
100
0
Order By: Relevance
“…With the aid of a Lyapunov-type theorem we obtain sufficient conditions on the parameters in (2.3) to ensure asymptotic mean-square stability of the zero solution of the recurrence equation. Related methods have been used in the case of stochastic delay differential equations in [2]. In [15] a general method is described to construct appropriate Lyapunov functionals and in fact, it is possible to construct different Lyapunov functionals giving different sets of sufficient conditions.…”
Section: Lyapunov Functionals For Stochastic Difference Equationsmentioning
confidence: 99%
“…With the aid of a Lyapunov-type theorem we obtain sufficient conditions on the parameters in (2.3) to ensure asymptotic mean-square stability of the zero solution of the recurrence equation. Related methods have been used in the case of stochastic delay differential equations in [2]. In [15] a general method is described to construct appropriate Lyapunov functionals and in fact, it is possible to construct different Lyapunov functionals giving different sets of sufficient conditions.…”
Section: Lyapunov Functionals For Stochastic Difference Equationsmentioning
confidence: 99%
“…Since most of these equations cannot be solved explicitly, numerical approximations become an important tool in studying the properties of these stochastic systems (see [1], [3], [10], [17], [20] and [26]). Since stability is one of the major concerns in systems analysis, the stability of numerical methods becomes also one of the main tools to examine the stability of the exact solution of the stochastic systems (see [18], [21] and [24]).…”
Section: Introductionmentioning
confidence: 99%
“…For delay differential equations or stochastic differential equations, stability conditions have been well investigated. However, for stochastic delay differential equations, only a few conditions were derived for exponential p-th moment stability (see [3]- [5] for example). In [6], almost sure stability was studied for a second order stochastic differential equation (with no delay) which is a model of a hinged supported inverted pendulum and showed that noise can enhance stability.…”
Section: Introductionmentioning
confidence: 99%